Queer representations in Chinese-language film and the cultural landscape - Chao, Shi-Yan (Asian visual cultures., 2020)
This book provides a cultural history of queer representations in Chinese-language film and media, negotiated by locally produced knowledge, local cultural agency, and lived histories. Incorporating a wide range of materials in both English and Chinese, this interdisciplinary project investigates the processes through which Chinese tongzhi/queer imaginaries are articulated, focusing on four main themes: the Chinese familial system, Chinese opera, camp aesthetic, and documentary impulse. Chao's discursive analysis is rooted in and advances genealogical inquiries: a non-essentialist intervention into the "Chinese" idea of filial piety, a transcultural perspective on the contested genre of film melodrama, a historical investigation of the local articulations of mass camp and gay camp, and a transnational inquiry into the different formats of documentary. This book is a must for anyone exploring the cultural history of Chinese tongzhi/queer through the lens of transcultural media